Factors Influencing Export Potencial of a Developing Country SMEs: A Study of Colombian Firms (2006)
The scarce participation of SMEs in exports produces interest in developing and promoting them. SMEs exports promotion is of special need and interest in developing countries where SMEs knowledge is low and where their development rebounds in many social and economic positive consequences. Within this context, this study constructs a model that identifies potential exporters among Colombian manufacturer SMEs. A comparison between the exporting companies (in their years prior to export) and non-exporting companies (that had no plans to export for the next three years) forms the basis of this study. Empirical representative evidence was obtained through 151 companies of the Colombian small manufacturing population. The results suggest that the participation in training and export support programs has a strong positive relation to the firm's export potential. The increase in sales by a company outside its local area and the increase in its assets before exporting demonstrate a greater capacity for international expansion. Colombian SMEs showed that their knowledge increases as a result of experience in the markets, export intention and commitment with the international operation. According to these results, managerial and policymaker implications are explored.